(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Vertebral hemangiomas (VH) are benign, slowly progressive vascular tumors arising from capillary and cavernous blood vessels. The social significance of VH is determined by its high prevalence, reaching 10–11% in the general population; the majority of cases occur between the ages of 30 and 60 years, with women accounting for 2/3 of all cases [2, 3].